2010
DOI: 10.1016/j.tsf.2010.06.049
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput optimization of adhesion in multilayers by superlayer gradients

Abstract: For adhesion measurements, the superlayer method has recently been developed: an overlayer under high compressive stress (Mo film in our case) provides the loading and drives interface delamination and buckling. We combined the superlayer method with thickness gradients for high throughput adhesion measurements. In this way, the effect of small modifications of interface chemistry on adhesion in multilayers can be assessed in a single test through the identification of the threshold thickness. We used this met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…By varying the deposition parameters, various buckle morphologies can be obtained. For the present samples, the delamination occurred at the interface between silver and the native silicon dioxide of the substrate [26] and the kinematics of buckle formation was easily recorded by optical microscopy, a 29 m wide TC progressing over one wavelength in about 28 s. The buckle propagation was consistent with usual observations [27], with one notable addition, however: It was observed that the tip of the semicircular buckle sags when the TC completes one half-rotation and the front caves in (Fig. 1, see the Supplemental Material for a movie of the buckle propagation [28]).…”
mentioning
confidence: 79%
“…By varying the deposition parameters, various buckle morphologies can be obtained. For the present samples, the delamination occurred at the interface between silver and the native silicon dioxide of the substrate [26] and the kinematics of buckle formation was easily recorded by optical microscopy, a 29 m wide TC progressing over one wavelength in about 28 s. The buckle propagation was consistent with usual observations [27], with one notable addition, however: It was observed that the tip of the semicircular buckle sags when the TC completes one half-rotation and the front caves in (Fig. 1, see the Supplemental Material for a movie of the buckle propagation [28]).…”
mentioning
confidence: 79%
“…It is believed that the interfacial reaction leads to a reduced ZnO subsurface enriched in O-vacancies which act as donors and increase the carrier concentration 1,2,6 . Next to its use to create ohmic contacts 1,2,[6][7][8][9][10][11][12] , titanium is also known to promote adhesion for noble metals within optical coatings deposited on multilayeredglazings [13][14] , to enhance the gas sensor properties of ZnO 15 and to set up resistive random access memories 16 . Changes in Ti/ZnO stacking as a function of temperature are crucial regarding the optimization of contact resistivity 1,2,6-12 , gas detection limit 17 and mechanical properties of coatings 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, an ultrathin Ti layer serves as an adhesion enhancer between the oxide and the noble metal. 3 In both cases, the origin of the peculiar electronic behavior and of the bonding reinforcement is under discussion. [4][5][6] The reduction of ZnO by Ti results in the creation of O vacancies in the ZnO, giving rise to reduced interfacial resistivity and n-doping.…”
mentioning
confidence: 99%